Albian–Cenomanian calcareous nannofossils from DSDP Site 364 (Kwanza Basin, Angola): Biostratigraphic and paleoceanographic implications for the South Atlantic. (May 2020) - Bruno, Mauro Daniel Rodrigues; Fauth, Gerson; Watkins, David K.; Savian, Jairo Francisco
Abstract: The Albian–Cenomanian was an interval of extreme warmth due to greenhouse climatic conditions, as well as significant changes in the paleogeography and paleoceanography of the oceans, which affected the evolution of marine ecosystems on a global scale. This study analyzed the calcareous nannofossil assemblages from 72 samples that were recovered from Site 364 (Kwanza Basin, Angola), which was drilled by the Deep Sea Drilling Project (DSDP) Leg 40. A total of 103 calcareous nannofossil species were recovered, enabling the identification of biozones (CC 8 to CC 10a; or BC 23 to UC 1b/UC 4a) allowing to assign an Albian–Cenomanian interval for the deposition of the studied section. The recovered assemblages have a subtropical-tropical affinity and are indicative of a surface water connection between the Central Atlantic and the South Atlantic oceans, that extends at least as far as offshore Angola. The area sedimentation was predominantly calcareous and pelagic during this interval, with the exception of the basal section, where Albian black shales interbedded with dolomitic and marly limestones were deposited. Throughout the section, high concentrations of TOC and sulfur and the presence of dissolution-susceptible species likely indicate low euxinic conditions for the Kwanza Basin. Dissolution is a significant process for Site 364 in the majority of the studied samples, although not to the point where species richness was severely impacted, as small amounts of dissolution-susceptible taxa were observed. Dissolution showed a marked decrease in intervals in which paleontological and geochemical data indicated an increase in surface water fertility/productivity. Highlights: Calcareous nannofossil display a subtropical-tropical paleobiogeographic affinity. Assemblage indicate a surface water connection between Central and South Atlantic. Biozones indicate the Albian–late Cenomanian interval at the bottom of Site 364. Paleontological and geochemical data indicate impact of carbonate dissolution.